In-hospital Heart Rate Reduction With Beta Blockers and Ivabradine Early After Recovery in Patients With Acute Decompensated Heart Failure Reduces Short-Term Mortality and Rehospitalization - Faragli, Alessandro; Tano, Giuseppe Di; Carlini, Caterina De; Nassiacos, Daniel; Gori, Mauro; Confortola, Giada; Lo Muzio, Francesco Paolo; Rapis, Konstantinos; Abawi, Dawud; Post, Heiner; Kelle, Sebastian; Pieske, Burkert; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: In the past years, heart rate (HR) has emerged as a highly relevant modifiable risk factor for heart failure (HF) patients. However, most of the clinical trials so far evaluated the role of HR in stable chronic HF cohorts. Aim of this multi-center, prospective observational study was to assess the association between HR and a therapy with HR modulators (beta-blockers, ivabradine or a combination of ivabradine and beta-blockers) at hospital discharge with patients’ cardiovascular mortality and re-hospitalization at 6 months in acutely decompensated HF patients. Material and Methods: We recruited 289 HF patients discharged alive after admission for HF decompensation from ten centres in Northern of Italy over nine months (from April 2017 to January 2018). Primary endpoint was the combination of cardiovascular mortality or re-hospitalizations for HF at 6 months. Results: At 6 months after discharge, 64 patients were readmitted (32%) and 39 patients died (16%). Multivariate analysis showed that HR at discharge ≥ 90 bpm (OR=8.47; p=0.016) independently predicted cardiovascular mortality, while a therapy with beta-blocker at discharge was found to reduce the risk of the composite-endpoint. In patients receiving HR modulators the event rates for the composite endpoint, all-cause mortality and cardiovascular mortality were lower than in patients not receiving HR modulators. Conclusions: HR at discharge ≥ 90 bpm predicts cardiovascular mortality, while a therapy with beta-blocker is negatively associated with the composite endpoint of cardiovascular mortality and hospitalization at 6 months in acutely decompensated heart failure patients. Patients receiving a HR modulation therapy at hospital discharge showed the lowest rate of cardiovascular mortality and re-hospitalization.